2002
DOI: 10.1186/1751-0147-43-49
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Boar and Semen Parameters on Motility and Acrosome Integrity in Liquid Boar Semen Stored for Five Days

Abstract: Kommisrud E, Paulenz H, Sehested E, Grevle IS: Influence of boar and semen parameters on motility and acrosome integrity in liquid boar semen stored for five days. Acta vet. scand. 2002, 43, 49-55. -Ninety ejaculates from a total of 76 AI boars were extended in Beltsville Thawing Solution (BTS). Boar identity, breed, weight of the ejaculate and sperm concentration were registered. Motility and acrosome integrity were assessed after storage at 16-18°C for 6, 30, 54, 78, and 102 h. Storage time had a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 15 publications
1
9
0
3
Order By: Relevance
“…Por otro lado, la concentración tiene una connotación negativa sobre la normalidad morfológica en dosis seminales (23). Lo anterior se explica por una disminución en la capacidad endógena del plasma seminal para eliminar la producción de radicales libres alrededor de cada espermatozoide eyaculado, lo que afecta la funcionalidad de las células, y esta varía entre cada eyaculado (25).…”
Section: Discussionunclassified
“…Por otro lado, la concentración tiene una connotación negativa sobre la normalidad morfológica en dosis seminales (23). Lo anterior se explica por una disminución en la capacidad endógena del plasma seminal para eliminar la producción de radicales libres alrededor de cada espermatozoide eyaculado, lo que afecta la funcionalidad de las células, y esta varía entre cada eyaculado (25).…”
Section: Discussionunclassified
“…Sperm motility in ejaculates is considered to be one of the most important ejaculate quality parameters (Kommisrud et al, 2002) that affects the fertilization potential of semen. The study has revealed the percentage of motile spermatozoa to range from 75.00% at five-day intervals between the successive ejaculate collections to 67.78% at one-day intervals.…”
Section: MMmentioning
confidence: 99%
“…Many factors including storage length, extender type, male effect, boar age and breed affect boar sperm quality. With respect to this, assessment of the capacity of a specific extender to maintain the quality of stored boar spermatozoa should also include DNA integrity [ 12 , 19 ], acrosome intactness [ 13 , 20 ], mitochondrial activity [ 21 ], bacterial contamination, pH determination [ 9 ], tyrosine phosphorylation [ 15 ] and apoptotic changes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%